Incumbent business model innovation under misperceived hypercompetition - Kristian J. Sund; Annesofie Lindskov (Journal of Business Models (JOBM), 2022)
Hypercompetition theory states that incumbent firms must restructure their organizations, resources, and product portfolios, as competitive advantages cannot be sustained over time. Yet, hypercompetition is rarer than many scholars and practitioners suggest. In this paper, we suggest that if managers misperceive the true state of competition in their industry, they run two potential risks. The first is to underestimate the competitive dynamics and to therefore focus too much on incremental changes to their existing business model. The second is to overestimate the dynamics and to waste resources on unnecessary radical business model innovation. In this chapter we discuss these risks in light of recent research on both hypercompetition and on incumbent business model innovation.
Keywords: 650; hypercompetition; sustainable competitive advantage; dynamic competition; technology-intensive sectors; performance